Improving diet assessment of Arctic terrestrial predators with the size of rodent mandibles. (26th January 2020) - Schmidt, E.; Fauteux, D.; Therrien, J.‐F.; Gauthier, G.; Seyer, Y.
Abstract: Predator–prey interactions can control population fluctuations of several terrestrial vertebrates and energy fluxes in food webs. Quantifying these interactions typically requires the number of prey consumed by predators to be known, but prey size is often ignored. We hypothesized that rodent mandibles, which are routinely found in predatory bird pellets and mammalian scats, could be used to accurately determine prey size and thus estimate biomass consumed by Arctic predators. We used 1863 lemmings and voles from museum and field specimens collected across the North American Arctic to relate three measurements of the dentary bone and one on the molar toothrow with individual body mass. When species and location of specimens are known, our results suggest that the body mass of small rodents can be estimated with high precision using the dentary bone measurements (average R 2 ranging from 0.73 to 0.81), especially for lemmings and Microtus voles. Body mass can also be estimated with reasonable precision using the dentary bone measurements even when species or location was unknown (0.71 ≤  R 2  ≤ 0.80). Equations to convert mandible size to body mass are provided for site‐ and species‐specific estimations. Geographic variations in the relationship between mandible size and body mass were found, suggesting potential effects of genetic isolation or interactions with the immediate environment on size. Using mandible measurements in prey remains allows more precise estimation of biomass consumed by predators, which is essential to quantify energy fluxes within ecosystems and examine resource partitioning among Arctic predators. Abstract : This study examines the ability to estimate prey (small rodents) size based on four different mandible measurements that can be measured from bones commonly found in predator scat or regurgitated pellets. Results suggest that regardless of whether or not location and species are known, the body mass of small rodents can be determined with high precise (average R 2 ranging from 0.71 to 0.80) using dentary bone measurements. Equations for site‐ and species‐specific estimations provided by this study enable researchers to better quantify biomass and energy fluxes between trophic levels in the Arctic.